2020
DOI: 10.1007/s12020-020-02464-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pancreas and lung neuroendocrine neoplasms: a case–control study

Abstract: Purpose Neuroendocrine neoplasia (NEN) has been displaying an incremental trend along the last two decades. This phenomenon is poorly understood, and little information is available on risk factor for neuroendocrine neoplasia development. Aim of this work is to elucidate the role of potentially modifiable risk factors for pancreatic and pulmonary NEN. Methods We conducted a case–control study on 184 patients with NEN (100 pancreas and 84 lung) and 248 controls. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…Findings of Hassan and colleagues on higher prevalence of NEN in patients whose first‐degree relatives developed any cancer 38 suggest a possible hereditary basis. A link between NEN and cancer in general was also suggested by other studies, 39,40 supposing a shared cancer predisposition. However, the concurrence with other cancers might also be due to age, as NEN cases predominantly occur in higher age groups 41 .…”
Section: Discussionsupporting
confidence: 68%
“…Findings of Hassan and colleagues on higher prevalence of NEN in patients whose first‐degree relatives developed any cancer 38 suggest a possible hereditary basis. A link between NEN and cancer in general was also suggested by other studies, 39,40 supposing a shared cancer predisposition. However, the concurrence with other cancers might also be due to age, as NEN cases predominantly occur in higher age groups 41 .…”
Section: Discussionsupporting
confidence: 68%
“…This meta-analysis included a study with lung NETs with liver metastasis [ 26 ]. Existing studies have found that lung NETs may have distinct characteristics compared to GEP NETs [ 34 , 35 ]. To further assess this, sensitivity analysis was conducted excluding the study, which did not affect the major findings of this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Jedoch sind eine positive Familienanamnese (erstgradige Verwandte mit Malignom jeglichen Typs), Rauchen und Alkoholabusus als Risikofaktoren sowohl mit funktionell aktiven als auch inaktiven PNET assoziiert 27 . Ebenso wird ein gehäuftes Auftreten bei Patienten mit Typ-II-Diabetes beobachtet 28 .…”
Section: Pankreatische Neuroendokrine Tumoren: Insulinom Und Gastrinomunclassified